Performance comparison of selection nanoparticles for insulation of three core belted power cables - Ahmed Thabet; Youssef Mobarak; Nourhan Salem; A. M. El-noby (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents an investigation on the enhancement of electrical insulations of power cables materials using a new multi-nanoparticles technique. It has been studied the effect of adding specified types and concentrations of nanoparticles to polymeric materials such as PVC for controlling on electric and dielectric performance. Prediction of effective dielectric constant has been done for the new nanocomposites based on Interphase Power Law (IPL) model. The multi-nanoparticles technique has been succeeded for enhancing electric and dielectric performance of power cables insulation compared with adding individual nanoparticles. Finally, it has been investigated on electric field distribution in the new proposed modern insulations for three-phase core belted power cables. This research has focused on studying development of PVC nanocomposite materials performance with electric field distribution superior to the unfilled matrix, and has stressed particularly the effect of filler volume fraction on the electric field distribution.